The relationship between the big five personality traits and job performance among employees at Jabatan Laut, Sarawak / Nur Amira Alia Roslan - Roslan, Nur Amira Alia (2018)
This research was done to find out the relationship between The Big Five Personality Traits and Job Performance of employees in Jabatan Laut, Sarawak. Total population for this study was 100 and 80 sample size were used. The researcher used convenience sampling technique and distributed the questionnaires to the respondents. A pilot test was done before the questionnaires were distributed to make sure all the items are reliable. From the previous studies, four out of five of The Big Five Personality Traits have a positive relationship with Job Performance which are Conscientiousness, Agreeableness, Openness to Experience, and Extraversion.Meanwhile, Neuroticism has a negative relationship with Job Performance. Based on this study, the researcher found that Conscientiousness, Agreeableness, Neuroticism, and Extraversion has a positive relationship with Job Performance. Openness to Experience has a very low and not significant relationship with Job Performance.